Copper(II) complexes with 1-methyltetrazole: new method for synthesis and properties - Bogatikov, Andrey N.; Degtyarik, Mikhail M.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2017)
A new approach for synthesis of copper(II) complexes with 1-methyltetrazole based on oxidative dissolution of metallic powdercopper in ethanol – HCl (ammonium thiocyanate) was developed. Composition and structure of the complexes prepared were studied by elemental analysis, X-ray diffraction and infrared spectroscopy in the middle (4000–400 cm–1)  and long wave (400–50 cm–1) field. In all complexes ligand shows monodentate coordination. Polymeric structure of complexes studied is formed due to bridging coordination of anions. Magnetochemical studies revealed that copper(II) chloride complexes a low-temperature ferromagnetic.
Keywords: monosubstituted tetrazole; complex compounds; direct synthesis; X-ray diffraction; IR-spectroscopy; magnetochemistry